1988
DOI: 10.3109/02813438809009293
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction May Induce Positive Changes in Life-style and in the Quality of Life

Abstract: Eighty-four male patients with a mean age of 56.4 years were subjected to a semistructured interview 12-21 weeks after acute myocardial infarction. Twenty-eight individuals (group A) perceived a considerably or somewhat improved total life situation, 39 patients an unchanged (group B) and 17 patients (group C) a somewhat or considerably worsened total life situation. In all groups there were appreciable alterations with respect to stress on the job, physical activity and intake of fat/calories. Sixty per cent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 5 publications
3
24
0
1
Order By: Relevance
“…Our results regarding female gender are consistent with the recent metaanalysis [34] demonstrating that women report greater PTG than men. However, previous studies in cardiac samples have generally found no relationship between PTG and sociodemographic characteristics [12,16,20,21,35]. The lack of relationship between PTG and patient characteristics may be due to the small sample size of those previous studies, particularly considering sociodemographic factors are shown to relate to PTG in the context of other health-related traumas [14,15].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our results regarding female gender are consistent with the recent metaanalysis [34] demonstrating that women report greater PTG than men. However, previous studies in cardiac samples have generally found no relationship between PTG and sociodemographic characteristics [12,16,20,21,35]. The lack of relationship between PTG and patient characteristics may be due to the small sample size of those previous studies, particularly considering sociodemographic factors are shown to relate to PTG in the context of other health-related traumas [14,15].…”
Section: Discussionmentioning
confidence: 88%
“…PTG is shown to relate consistently to adaptive coping strategies [20] and positive health behaviours [12,21,22], which may explain its association with positive outcomes. Indeed, a qualitative study of female cardiac patients revealed 'Getting Health Care' as one of the four themes which emerged from the open-ended question of whether participants experienced positive effects post-myocardial infarction [19].…”
Section: Ptg and Health Service Usementioning
confidence: 97%
“…Two reports by Laerum and colleagues (Laerum et al, 1987; Laerum et al, 1988) describe the results of qualitative interviews with male post-MI patients 3 to 5 months post-MI. The authors found that a meaningful proportion of patients experienced gratitude, enjoyment of recreational activities, and love toward family.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we selected a gratitude letter because gratitude is common post-ACS (Laerum et al 1988), because post-ACS patients in our qualitative interviews felt that exercises focused on gratitude may be useful, and because this exercise (in a cohort of medical psychiatry patients) received the highest ratings of utility out of 9 total exercises (Huffman et al 2014a). We chose the personal strengths exercise for similar reasons: post-ACS patients had been particularly interested in exercises focused on cultivating strengths, and this exercise had performed well in our prior work.…”
Section: Methodsmentioning
confidence: 99%